Crack propagation in filled elastomers: 3D study of mechanisms involving the filler agglomerates. (15th October 2022) - Kallungal, Jesbeer; Chazeau, Laurent; Chenal, Jean-Marc; Adrien, Jérôme; Maire, Eric; Barrès, Claire; Cantaloube, Bernard; Heuillet, Patrick; Wilde, Fabian; Moosmann, Julian; Weitkamp, Timm
Graphical abstract: Crack propagation mechanism in the presence of carbon black agglomerates in the crack tip vicinity (CB agglomerates undergoes fracture under strain) Highlights: In filled EPDM, carbon black agglomerates are aggregates/elastomer clusters. They are soft and deformable and can undergo fracture. This fracture in the vicinity of the crack tip causes additional energy dissipation. This slows down crack propagation speed at high strain energy release rate. Abstract: This paper presents the impact of Carbon Blacks agglomerates, at different concentrations, on crack propagation mechanisms in a Carbon black (CB) filled Ethylene Propylene Diene Monomer (EPDM) elastomer. As shown by Transmission electron microscopy, these CB agglomerates (CBaggl ) consist of aggregates clusters with interpenetrating elastomer, and for this reason, are soft and deformable. Crack tip observation using X-ray tomography demonstrates that these CBaggl can either undergo fracture or arrest/ deviate a crack during its propagation. This causes higher energy dissipation at the crack tip, which contributes to the dissipative component of the strain energy release rate G. For this reason, it is found that among the two materials tested with a significant amount of CBaggl (more than 3%), the material with the highest concentration has a slower crack propagation speed at high G.